"We are not phobic but selective": the older generation's attitude towards using technology in workplace communications. Issue 4 (2nd June 2014) - Singh, Vibhav
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study and understand the older generation's attitude toward use of technology for workplace communications. Design/methodology/approach – In-depth interviews were conducted with the older generation employees of an Indian Oil and Gas Public Sector Undertakings. Data gathered from the interviews were then analyzed to draw broad themes. Findings – Although the older generation is aware of the importance of technology and has adequate knowledge of its use, they are reluctant to use it. The reluctance is not on account of techno-phobia; it is more in the nature of approach-avoidance. Research limitations/implications – Organizations and human resource managers should focus on addressing the mental block of the older generation regarding the use of technology. Practical implications – Reverse mentoring and formation of cross-generational teams can be used to alter older generation's selective mindset in relation to technology. Originality/value – This paper discusses the role of technology in intergenerational communication in the Indian context.